L’interaction Micro-Assurances Et Assurés Dans Le Processus De Couverture Maladie En Côte d’Ivoire - Memon, Fofana; Komenan, Kouame (European Scientific Journal, ESJ, 2016)
The micro health insurance have greatly contributed to the medical coverage of the Ivorian population. This text is to question the social behavior of micro-insurance and insured to explain how they disrupt the disease process coverage of the individual. In terms of methodology, this article is based on a qualitative approach based on direct and indirect observation, document review and interviews. The results of the study indicate that microinsurance disease involved, certainly, to improve access of the population to health but the behavior of the insurer and the insured may hinder access to care health. This is the adverse selection behavior that the study seen at the micro-insurance and skilled behavior of moral hazard at the insured.